2018
DOI: 10.1016/j.celrep.2018.02.098
|View full text |Cite
|
Sign up to set email alerts
|

Differential Occupancy of Two GA-Binding Proteins Promotes Targeting of the Drosophila Dosage Compensation Complex to the Male X Chromosome

Abstract: Little is known about how variation in sequence composition alters transcription factor occupancy to precisely recruit large transcription complexes. A key model for understanding how transcription complexes are targeted is the Drosophila dosage compensation system in which the male-specific lethal (MSL) transcription complex specifically identifies and regulates the male X chromosome. The chromatin-linked adaptor for MSL proteins (CLAMP) zinc-finger protein targets MSL to the X chromosome but also binds to GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(93 citation statements)
references
References 50 publications
8
85
0
Order By: Relevance
“…To evaluate this prediction and define factors that might contribute to this behavior, we computationally assessed a comprehensive repertoire of ChIP-seq data (Baumann and Gilmour, 2017;Henriques et al, 2018;Ho et al, 2014;Kaye et al, 2018;modENCODE Consortium et al, 2010;Weber et al, 2014). Specifically, we sought to identify factors enriched (or de-enriched) at gene promoters where pausing is unstable as compared to other promoters (see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate this prediction and define factors that might contribute to this behavior, we computationally assessed a comprehensive repertoire of ChIP-seq data (Baumann and Gilmour, 2017;Henriques et al, 2018;Ho et al, 2014;Kaye et al, 2018;modENCODE Consortium et al, 2010;Weber et al, 2014). Specifically, we sought to identify factors enriched (or de-enriched) at gene promoters where pausing is unstable as compared to other promoters (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive repertoire of ChIP-seq datasets from (Baumann and Gilmour, 2017;Henriques et al, 2018;Kaye et al, 2018;Lim et al, 2013;Weber et al, 2014) and…”
Section: Features Associated With Genes With Short-lived Promoter Polmentioning
confidence: 99%
“…Since Larschan and colleagues suggested some competition in DNA-binding between CLAMP and GAF (Kaye et al, 2018), we explored whether the two proteins compete for binding to HAS in vivo. Upon RNAi depletion of GAF in male S2 cells the CLAMP ChIP-seq signal was unchanged at HAS (Figs.…”
Section: Msl2 Requires Clamp For Efficient Binding To Has In Vivomentioning
confidence: 99%
“…This assay locates the MSL2 interaction site to an Nterminal fragment of CLAMP, which harbors the first ZnF domain. The remaining 6 C-terminal ZnF domains are involved in binding to GA-dinucleotide repeats (Kaye et al, 2018;Kuzu et al, 2016;Soruco et al, 2013). Using various C-terminal deletion constructs of MSL2 showed that the ~200 C-terminal amino acids downstream of the CXC domain are required for interaction with CLAMP (Appendix S5A).…”
Section: Clamp and Msl2 Form A Stable Complexmentioning
confidence: 99%
“…CLAMP acts locally at CES/HAS sites and at a distance with GAF to recruit the MSL complex and to shape the overall architecture of the X chromosome [22][23][24] .…”
Section: Resultsmentioning
confidence: 99%